Saltar la navegación

Simples 2

1) \(y=20x^3-12x+\dfrac 8 {10} \) 2) \(y=9^x + \log_2 x+7\)
3) \(y=\sqrt[9]x + 10x-9\) 4) \(y=e^x+1\)
5) \(y=4x \cos x\) 6) \(y=\dfrac {10x}{\sin x}\)
7) \(y=\dfrac{x^2}{2}+\dfrac{x^10}{2}\) 8) \(y=-6x \ln x\)
9) \(y= \dfrac {\ln x} x \) 10) \(y=\dfrac 1 {2x+2}\)

Soluciones

Soluciones

1

\[ y'=60x^2-12\]

2

\[ y'=9^x \cdot \ln 9 + \frac 1 {x \ln 2}\]

3

\[ y'=\dfrac 1 {9 \sqrt[9]x^7}+10\]

4

\[ y'=e^x\]

5

\[ y'=D(4x) \cdot \cos x + D(\cos x) \cdot 4x\]

\[ y'=4  \cdot \cos x - \sin x \cdot 4x\]

6

\[y'= \frac {D(10x) \cdot \sin x - D(\sin x) \cdot 10x }{(\sin x)^2}\]

\[y'= \frac {10 \cdot \sin x - \cos x \cdot 10x }{\sin^2 x}\]

7

\[ y'=\frac {D(x^2)}{2} +0\] No es necesario derivarlo como una división ya que en el denominador no hay x.

\[ y'=\frac {\not 2x}{\not 2} \]

\[ y'=x \]

8

\[ y'=D(-6x) \cdot \ln x + D(\ln x) \cdot (-6x) \]

\( y'= -6 \cdot \ln x + \dfrac 1 x \cdot (-6x) \)

\[ y'= -6 \ln x + \frac {-6x} x  \]

\[ y'= -6 \ln x -6\]

9

\[ y' = \frac {D(\ln x) \cdot x - D(x) \cdot \ln x}{x^2}  \]

\[ y' = \frac {\dfrac 1 x  \cdot x - 1 \cdot \ln x}{x^2}  \]

\[ y' = \frac {\dfrac x x   - \ln x}{x^2}  \]

\[ y' = \frac {1  - \ln x}{x^2}  \]

10

\[y'=\frac {D(1) \cdot (2x+2) - D(2x+2) \cdot 1}{(2x+2)^2}\]

\[y'=\frac {0 \cdot (2x+2) - 2 \cdot 1}{(2x+2)^2}\]

\[y'=\frac {- 2 }{(2x+2)^2}\]